The crystal structure of di-tert-butyl dicarbonate, C10H18O5 - Manana Pholani; Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures)
C10H18O5, monoclinic, P21/c (no. 14), a = 11.3561(7) Å, b = 11.4569(7) Å, c = 10.9762(6) Å, β = 116.087(2)°, V = 1282.58(13) Å3, Z = 4, Rgt(F) = 0.0547, wRref(F2) = 0.1677, T = 200 K.